The Influence of Perceived Organizational Support, Transformational Leadership, and Work Motivation on Teacher Performance at XYZ Elementary School, North Jakarta - Violent Hennyta; Niko Sudibjo (Eduvest - Journal of Universal Studies, 2024)
A school is an organization that operates in the field of education as a place where the learning process occurs for students to obtain education from teachers. Teachers at the forefront have an important role in advancing and improving services in schools. To support optimal performance, it is very important for a school leader to have strong organizational support, good abilities in managing the school, and able to increase and maintain teacher motivation. Researchers conducted to find out how perceived organizational support, transformational leadership, and work motivation influence teacher performance at SD XYZ North Jakarta. This research uses a quantitative research approach using the PLS-SEM method to analyze the influence of path coefficients on the variables studied. The respondents of this research were all 118 teachers at SD XYZ North Jakarta who filled out a survey using saturated sample data collection via the Google Form application. The data obtained was analyzed using SEM (Structural Equation Modeling) with the PLS 3.0 application. The results of this research show that perceived organizational support, transformational leadership, and work motivation have a positive effect on teacher performance.